Pengaruh Independensi, Pengalaman Kerja, Due Profesional Care, dan Akuntabilitas terhadap Kualitas Audit di KAP Malang - Muhammad Faris Nugraha; M. Cholid Mawardi; Arista Fauzi Kartika Sari (Universitas Islam Malang, 2023)
This study aims to determine the effect of independence, work experience, due professional care, and accountability on audit quality in Malang. The independent variables in this study are independence, work experience, due professional care, and accountability while the dependent variable is audit quality. This type of research is quantitative research, because the data used is in the form of numbers and numbers. . Source of data in this study is primary data with data collection methods in the form of questionnaires. The population in this study are auditors who are in KAP Malang City. The data collection technique uses the slovin formula. Based on this method, the number of auditors used is 79 respondents. The hypothesis was tested using descriptive statistical analysis, instrument testing, normality test, classical assumption test, multiple linear regression analysis test, and hypothesis testing using SPSS Version 25. The results showed that the Independence variable had a positive effect on audit quality (0.000 <0.05), the work experience variable has no effect on audit quality (0.073 > 0.05), the due professional care variable has a positive and significant effect on audit quality (0.000 <0.05) and the accountability variable has a positive and significant effect on audit quality (0.041 <0.05 ).Keywords: Independence, Work Experience, Due Professional care, Accountability, Audit quality.